2014
DOI: 10.3109/09637486.2014.898257
|View full text |Cite
|
Sign up to set email alerts
|

Effect of maternalChlorellasupplementation on carotenoid concentration in breast milk at early lactation

Abstract: Breast milk carotenoids provide neonates with a source of vitamin A and potentially, oxidative stress protection and other health benefits. Chlorella, which has high levels of carotenoids such as lutein, zeaxanthin and β-carotene, is an effective dietary source of carotenoids for humans. In this study, the effect of maternal supplementation with Chlorella on carotenoid levels in breast milk at early lactation was investigated. Ten healthy, pregnant women received 6 g of Chlorella daily from gestational week 16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 26 publications
0
23
0
Order By: Relevance
“…Several studies have analyzed the carotenoid content in human breast milk across diverse populations worldwide [237,[240][241][242][243][244][245][246][247][248][249][250]. These findings demonstrate a strong correlation between dietary intake of carotenoids and the content found in breast milk [178,251,252].…”
Section: Carotenoidsmentioning
confidence: 83%
“…Several studies have analyzed the carotenoid content in human breast milk across diverse populations worldwide [237,[240][241][242][243][244][245][246][247][248][249][250]. These findings demonstrate a strong correlation between dietary intake of carotenoids and the content found in breast milk [178,251,252].…”
Section: Carotenoidsmentioning
confidence: 83%
“…Another main source of carotenoids is the green alga Haematococcus pluvialis , for which cultures have developed industrially in several countries (Cysewski and Lorenz 2004). Carotenoid supplements, including β-carotene, are effective in improving the carotenoid supply in breast milk at early lactation (Nagayama et al 2014). However, the optimal levels of β-carotene remain controversial.…”
Section: Phytochemicalsmentioning
confidence: 99%
“…Chlorella has high levels of carotenoids such as lutein, zeaxanthin, and β-carotene is an effective dietary source of carotenoids for humans. Nagayama et al (2014) reported Chlorella intake during pregnancy is effective in improving the carotenoid status of breast milk at early lactation. Breast milk carotenoids provide neonates with a source of vitamin A and potentially, oxidative stress protection, and other health benefits.…”
Section: Agriculture Industrymentioning
confidence: 99%